Data protection as a part of cyber security - Čapek, Jan (Trauner Verlag, 2017)
Introduction of computers in all spheres of life substantially changed the ways of how people communicate and exchange information. It is creating a virtually paperless work environment. Keyless Signatures Infrastructures are an alternative solution to traditional PKI signatures. Storing and safely sending a large amount of information is a problem on one side, on the other hand increasing communication between things (for example smart cars, consumer houses etc.) requires a secure exchange of information where the blockchanging method is promising.
Ochrana dat jako část kybernetické bezpečnosti
Keywords: Cybersecurity; Data protection; Blockchain technology; Hash function.; Kybernetická bezpečnost; Ochrana dat; Technologie zřetězení; Hash funkce.